Upper gastrointestinal endoscopy findings in patient presenting with dyspepsia - Shrestha, Roshan; Karki, Sanjit; Pandey, Bimal; Sharma, Yuba Raj (Journal of Patan Academy of Health Sciences, 2015)
Introductions: The objective of this study was to evaluate the upper gastrointestinal endoscopy findings in patients presenting with dyspepsia. Methods: This retrospective observational study was conducted in Department of Internal Medicine, Patan Hospital from April 2013 to March 2014. Adult patients who underwent upper gastrointestinal endoscopy for dyspepsia were included in the study. Results: There were 2141 endoscopies (out of total 3195) performed for dyspepsia, male 996 (46.52 %), female 1145 (53.48%), mean age 39.37 years (SD ± 18.16). A single endoscopic diagnosis was made in 1991 (93%) and in rest, combinations of lesions were seen. Gastritis 892 (41.66%), oesophagitis 215 (10.04%), duodenal ulcer 100 (4.67%), gastro-duodenitis 85 (3.97%), hiatus hernia 82 (3.82%), gastric ulcer 46 (2.14%) and no lesions in 594 (27.74%) were seen. Conclusions: Gastritis followed by oesophagitis was seen in half of the dyspeptic, while a quarter had functional dyspepsia with normal findings. Journal of Patan Academy of Health Sciences, Vol. 2, No. 2, 2015. page: 19-22